Case Report: A neonatal case of cryopyrin-associated periodic syndrome with severe funisitis and neonatal asphyxia - Hayashida, Yuri; Hatano, Maho; Ito, Kazuyuki; Sugie, Manabu; Kunieda, Junko; Shimizu, Masaki; Morio, Tomohiro; Morioka, Chikako (Frontiers in Pediatrics, 2024)
Cryopyrin-associated periodic syndrome (CAPS) is a genetic disorder and autoinflammatory disease characterized by chronic inflammation throughout the body. The most severe form of CAPS, Chronic Infantile Neurologic Cutaneous, and Articular (CINCA) syndrome, also known as Neonatal Onset Multisystem Inflammatory Disease (NOMID), has three main features: skin rash, CNS involvement, and joint symptoms. Although these symptoms are typically reported shortly after birth, there have been a few reports of prenatal inflammation. Here, we report our experience managing a case of a CAPS infant born in severe neonatal asphyxia due to a ruptured cord associated with severe funisitis. The baby was born at 38 weeks and 6 days of gestation, weighing 2898 g, through an ultra-emergency Caesarian section prompted by variable deceleration. The Apgar score was 1 point at 1 minute and 4 points at 5 minutes, necessitating intensive care due to hypoxic-ischemic encephalopathy. Upon delivery, it was observed that the umbilical cord had partially ruptured at the site of attachment to the baby, accompanied by arterial hemorrhage. Umbilical cord rupture was considered to be the cause of the sudden decrease in fetal heart rate. Pathological examination also showed that the inflammation of the cord was more severe on the side attached to the fetus and on the arterial side, suggesting that the inflammation had extended from the fetus. The father carried a genetic mutation associated with CINCA syndrome/NOMID (NLRP3 c.2068G>A p.Glu690Lys Hetero), which was also found in the child. Histopathologic examination of the placenta and umbilical cord can provide crucial insights into the intrauterine onset of inflammation, which is the first manifestation of CINCA syndrome/NOMID in newborns. It should be noted that births with a genetic predisposition to CAPS may have complications related to the placenta and umbilical cord.